Miejsce polskich regionów w europejskiej przestrzeni regionalnej ze względu na poziom GOW - Strahl, Danuta; Markowska, Małgorzata (The Position of Polish Regions in European Regional Space with Regard to the Level of Knowledge Based Economy, 2008)
The article presents the proposal of analytical procedure aimed at quantification of knowledge based economy (KBE) level, in the sector of industry and services, in regional dimension. Additionally, the article identifies the position of Polish NUTS-2 level regions in European regional space regarding KBE level, considering the following factors: share of the employed tertiary education graduates in the overall number of population aged 25-64, share of population participating in continuous education in the overall population number aged 25-64, number of patents per 1 million of work force, share of the employed in high and mid-tech industry in the overall number of workers, share of the employed in high and mid-tech industry in the overall number of workers employed in industry sector, share of the employed in knowledge-intensive services in the overall number of workers, share of the employed in knowledge-intensive services in the overall number of workers employed in services. (original abstract)
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 3, s. 15-34